Design and synthesis of a magnesium alloy for room temperature hydrogen storage. (1st May 2018) - Edalati, Kaveh; Uehiro, Ryoko; Ikeda, Yuji; Li, Hai-Wen; Emami, Hoda; Filinchuk, Yaroslav; Arita, Makoto; Sauvage, Xavier; Tanaka, Isao; Akiba, Etsuo; Horita, Zenji
Abstract: Safe and high-density storage of hydrogen is a key issue for development of hydrogen as a clean energy carrier. Hydride-forming materials are potential candidates for safe and high-density storage of hydrogen and among them; Mg-based alloys are the most investigated ones due to their high gravimetric capacity. The key issue for practical application of Mg-based alloys is that they do not desorb hydrogen without heating due to the strong hydrogen binding energy. In this study, we employed first-principles calculations to design a Mg-based alloy with a low hydrogen binding energy and room temperature hydrogen storage properties. The designated material, highly-homogenous Mg4 NiPd with a BCC-based CsCl-type structure, was successfully synthesized by severe plastic deformation via the high-pressure torsion (HPT) method. The alloy exhibited reversible hydrogenation and dehydrogenation at room temperature with high phase stability. This discovery introduces a rational approach to design and synthesize new alloys for hydrogen storage using the concept of binding energy engineering. Graphical abstract: Image 1